2019
DOI: 10.1016/j.reth.2019.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The period circadian clock 2 gene responds to glucocorticoids and regulates osteogenic capacity

Abstract: Introduction The central regulatory system that generates biological rhythms is regulated by circadian clock genes expressed by cells in the suprachiasmatic nucleus. Signals from this system are converted to adrenocortical hormones through the sympathetic nervous system and transmitted to peripheral organs. Another system releases glucocorticoids (GCs) in response to stress through the HPA-axis. Here we investigated the second messenger GC, which is shared by these systems and influences the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Honma et al [ 32 ] found that PER2 is a directly target gene of DEX. Abe et al [ 33 ] revealed that PER2 is required for the maturation of bone tissue. In this study, we suggested that PER2 directly regulating FGF2 through STITCH network.…”
Section: Discussionmentioning
confidence: 99%
“…Honma et al [ 32 ] found that PER2 is a directly target gene of DEX. Abe et al [ 33 ] revealed that PER2 is required for the maturation of bone tissue. In this study, we suggested that PER2 directly regulating FGF2 through STITCH network.…”
Section: Discussionmentioning
confidence: 99%
“…A single injection of dexamethasone could restore the circadian rhythm of osteoclast-related genes such as cathepsin K ( Ctsk ) in adrenalectomized mice ( 66 ). Per2 knock-out mice could not restore the GC-induced bone loss despite a bisphosphonate (Zoledronic acid) treatment, although Per2 knock-out osteoblasts showed an increased proliferation capacity ( 68 ).…”
Section: Circadian Rhythmicity and Gcsmentioning
confidence: 99%
“…19,26 Mutations in mice's CRY and PER genes led to increased osteoblast activity and bone mass. 33, 34 In addition to acting on osteoclasts, CRY2 is also crucial for the stability of the extracellular cartilage matrix. PER2 is vital for bone maturation, and the PER2 mutation promotes osteoblast proliferative activity.…”
Section: The Function Of Cry and Per In Osseointegrationmentioning
confidence: 99%